Baelo Claudia dans l’Antiquité tardive - Laurent Brassous (Mélanges de la Casa de Velázquez, 2017)
The archaeological investigations carried out to the south-east of the forum of the Roman town of Baelo Claudia have uncovered a number of phases in the monumental sector indicating reform, abandonment and reoccupation between the 3rd and 6th centuries. The structures uncovered, along with numerous associated objects and materials (coins, ceramics, glass, metal, fauna, etc.) throw new light on the history and the condition of the site in late antiquity, which between the end of the 4th century and its final abandonment in the 6th century resembled that of a large village rather than a town.